How sanctions on Russia and Belarus are impacting exports of agricultural products and fertilizer - Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
The sanctions imposed by the European Union, United States, Canada, and other countries on Russia and Belarus following Russia’s February 24 invasion of Ukraine included restrictions on banking, trade, technology transfers, and specific individuals. These came on top of earlier sanctions on both countries — on Russia, in response to its 2014 annexation of Crimea, and on Belarus, in response to human rights violations in 2020 and its forced grounding of Ryanair flight 4798 to seize a dissident journalist in 2021. The current sanctions regime aims to spare the agriculture sector, including inputs, to avoid side effects on global food security. Russia is a major global supplier of key staples, including wheat, and both countries are important fertilizer producers and exporters. Shutting down trade in those items would have disastrous consequences for global markets and on agriculture and food supplies in countries reliant on them.